Yoga: A New dimension in fostering India-Africa engagement (International Journal of Food and Nutritional Sciences, 2022)
Yoga has been a practice of self-awareness, self-knowledge, and self-actualization for wellbeing of human at physical, mental, emotional, behavioral, spiritual and psychological level, since 300 BCE or even earlier. Its practices are thought to date back to pre-Vedic Indian traditions, possibly to the Indus valley civilization. The objective of this research paper is to explore how the practice of yoga is being a new domain of cooperation between India and Africa. Yoga is helping India to strengthening its ties with African nations. Similarly, yoga is helping African countries in not only to lead a healthy life but also helping African countries in empowering them economically and socially. For analysis of these research objectives, I will be using secondary sources and descriptive method of study, which would be concluded by exploring all the possible dimensions of how yoga is contributing in fostering India-Africa cooperation.